فقه السيرة النبوية في العهد المكي من خلال كتاب فتح الباري شرح صحيح البخاري لابن حجر العسقلاني (المتوفى-852) (دراسة وصفية تحليلية): Understanding of the Prophet (PBUH)’s Biography In the era of Mecca in the book Fath Al- Bari explanation of Sahih Al- Bukhari by Imam Ibn - e - Hajar Alasqalani (died 852AH) (An analytical & descriptive study) (Al-Aasar, 2025)
The book “Fath Al- Bari explanation of Sahih Al –Bukhari” written by Imam Ibn - e - Hajar Alasqalani, is an important source of the Prophet’s ﷺ biography. It is a magnum opus to understand the intelligence and wisdom of Prophet’s ﷺ life. The author’s methodology is not limited to narrate mere events and incidents of seerat un Nabiﷺ, Instead he elucidates different happenings from Holy birth of Prophet ﷺ to his migration towards Madina.Writer also annotates research about Prophet’sﷺ clan i.e.Quraish and his dealing with the people of different civilization during Hajj days. In this article, I am going to explain the details of blessed merriage of Prophet ﷺ with Sayyida Khadija RA from Fath Al- Bari explanation of Sahih Al –Bukhari moreover I have tried to deduce the valuable lessons from it,in order to apply these rules and derivatives in solving the current problems in our individual and collective life.